Pressure-induced metallization in MoSe2 under different pressure conditions. Issue 10 (15th February 2019) - Yang, Linfei; Dai, Lidong; Li, Heping; Hu, Haiying; Liu, Kaixiang; Pu, Chang; Hong, Meiling; Liu, Pengfei
Abstract : Our experimental results clearly indicate that the metallization behavior of MoSe2 exhibits significant dependence on the pressure environments. Abstract : In this study, the vibrational and electrical transport properties of molybdenum diselenide were investigated under both non-hydrostatic and hydrostatic conditions up to ∼40.2 GPa using the diamond anvil cell in conjunction with Raman spectroscopy, electrical conductivity, high-resolution transmission electron microscopy, atomic force microscopy, and first-principles theoretical calculations. The results obtained indicated that the semiconductor-to-metal electronic phase transition of MoSe2 can be extrapolated by some characteristic parameters including abrupt changes in the full width at half maximum of Raman modes, electrical conductivity and calculated bandgap. Under the non-hydrostatic condition, metallization occurred at ∼26.1 GPa and it was irreversible. However, reversible metallization occurred at ∼29.4 GPa under the hydrostatic condition. In addition, the pressure-induced metallization reversibility of MoSe2 can be revealed by high-resolution transmission electron and atomic force microscopy of the recovered samples under different hydrostatic conditions. This discrepancy in the metallization phenomenon of MoSe2 in different hydrostatic environments was attributed to the mitigated interlayer van der Waals coupling and shear stress caused by the insertion of pressure medium into the layers.